IMPROVING WETTABILITY OF POLYCARBONATE AND ADHESION WITH ALUMINUM BY AR+ ION IRRADIATION - KOH, SK; SONG, SK; CHOI, WK; JUNG, HJ; HAN, SN (MATERIALS RESEARCH SOCIETY, 1995)
Improving wettability of the polycarbonate (PC) surface to triple distilled water has been carried out by Ar+ ion irradiation with blowing oxygen gas. The amount of Ar+ was changed from 10(14) to 5 X 10(16) ions/cm(2) at 1 keV energy by a Kaufman-type ion source. Contact angle of the water to PC has been reduced from 78 degrees to 50 degrees with Ar+ irradiation, and to 12 degrees with Ar+ irradiation in various vacuum pressures adjusted by oxygen gas flow rate (0-4 seem). Strong O-H stretching vibration peaks at about 3370 cm(-1) on FT-IR spectra of the polymer appeared after the surface treatments, and the wetting angle of the treated PC was returned to its value (78 degrees) when the PC was exposed in air environment. The minimum contact angles were maintained with the same value when the irradiated polymers were kept in dilute HCl solution. The improved wettability and surface chemical reaction by Ar+ ion irradiation with oxygen was explained by the formation of a hydrophilic functional group. Enhanced adhesion between aluminum and PC was confirmed by the scotch tape test, and was discussed with relation between the hydrophilic group on the polymer surface and the deposited metal.
Keywords: THIN-FILM ADHESION; BEAM-ENHANCED ADHESION; SURFACE MODIFICATION; POLYIMIDE SUBSTRATE; POLY(ETHYLENE-TEREPHTHALATE); CRYSTALLINITY; RADIATION; POLYMERS